(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is about works created for the choir cappella based on the folk musical heritage. “Choirs” are emotionally imaginative for folk songs of various ethnic origin (uzbek, tajik, kazakh, uygur and karakalpak) depending on the time of their appearance (among them ancient and modern). Content and beautiful beauty, happiness based on songs of mutual love. And joy, the renewal of life and nature.